2017
DOI: 10.5935/0004-2749.20170027
|View full text |Cite
|
Sign up to set email alerts
|

Iris-claw intraocular lens implantation in children with ectopia lentis

Abstract: Compared with previous similar studies, this study utilized the largest pediatric patient group and had the longest post-surgery follow-up time. Moreover, it is advisable that pediatric patients with non-traumatic ectopia lentis be carefully screened for any underlying hereditary disease, especially diseases related to connective tissue metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“… 30 , 70 The risk of redislocation tends to be more among young patients (<55 years of age) and those with a trauma history. 15 , 34 , 43 Three randomized clinical trials by Dalby et al, Kristianslund et al, and Helvaci et al, involving patients >55 years of age, observed redislocation at a rate of 3%, 2%, and 0%, respectively. 14 , 16 , 24 Shuaib et al reported a disenclavation rate of 20% (mean follow-up of 6 months), and Cevik et al experienced a disenclavation rate of 37% (mean follow-up of 38 months).…”
Section: Postoperative Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“… 30 , 70 The risk of redislocation tends to be more among young patients (<55 years of age) and those with a trauma history. 15 , 34 , 43 Three randomized clinical trials by Dalby et al, Kristianslund et al, and Helvaci et al, involving patients >55 years of age, observed redislocation at a rate of 3%, 2%, and 0%, respectively. 14 , 16 , 24 Shuaib et al reported a disenclavation rate of 20% (mean follow-up of 6 months), and Cevik et al experienced a disenclavation rate of 37% (mean follow-up of 38 months).…”
Section: Postoperative Outcomesmentioning
confidence: 99%
“…The frequency of CME following ICIOL implantation depends on the indication for surgery and ranges from 0%-25%. 14–18 , 20–32 , 34–39 , 41–44 , 46–56 The duration of follow-up, sample size, and investigative method for CME in different studies also affect the CME rates. Use of OCT at regular follow-ups after cataract surgery might be useful in detecting non-clinical CME (<20/40 change in CDVA).…”
Section: Postoperative Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that Artisan provides good results in terms of improving uncorrected and corrected vision, but involves a high incidence of postoperative complications, especially lens dislocation and retinal detachment. [35]…”
Section: Introductionmentioning
confidence: 99%